PROFILING INTELLECTUAL CAPITAL PERFORMANCE AND RETURN ON INVESTED CAPITAL: EVIDENCE FROM INDUSTRIAL INDONESIAN BANKING - Elen Puspitasari; Bambang Sudiyatno Sudiyatno; Gregorius Masdjojo; Wahyu Meiranto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this research is to profiling Return on Invested Capital and Intellectual Capital Performance by conducting tests and analyzing their effects on Industrial of Indonesian Banking. Measuring a company efficiency in allocating capital to profitable investments gives a sense of how well a company is using capital to generate profits. The main of finding is to asses return on invested capital become more informative as a financial performance. The research population consisted of 124 banking companies listed on IDX. Based on the sample selection criteria, we obtained 99 observational data samples. The method of analysis in this research was a quantitative method using program Eviews-Econometric Views. The analysis technique used in this research was panel data regression analysis. The results of this research show that human capital efficiency has a significant but negative effect on return on invested capital. Structural Capital Efficiency has a significant and positive effect on Return On Invested Capital. Capital Employed Efficiency has no significant effect on Return on Invested Capital. This study applied Resource Based Theory to develop the research hypotheses. This research novelty is the use Indonesian Banking Industry for profiling their return on invested capital and three angels efficiency, which consist of human, structural and capital employee.